2021
DOI: 10.1101/2021.07.05.451164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracing the evolution of human gene regulation and its association with shifts in environment

Abstract: As humans spread throughout the world, they adapted to variation in many environmental factors, including climate, diet, and pathogens. Because many of these adaptations were likely mediated by multiple non-coding variants with small effects on gene regulation, it has been difficult to link genomic signals of selection to specific genes, and to describe the regulatory response to selection. To overcome this challenge, we adapted PrediXcan, a machine learning method for imputing gene regulation from genotype da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…For the #5 "gene regulation" cluster, an ML modality was adapted by Colbran et al to impute gene regulation information from genotype data and investigate 490 ancient Eurasian human DNA samples and explore divergent gene regulation mechanisms which contributed to skin pigmentation and metabolic and immune functions. The authors identified gene regulation roles in adaptation and associations between complex traits and genetic diversity Colbran et al, (2021). Atak et al devised a deep learning approach and integrative genomics strategy to analyze functional enhancer mutations with allelic imbalance of gene expression and chromatin accessibility and successfully interpreted and predicted the impact of a mutation on gene regulation Atak et al, (2021).…”
Section: The Knowledge Base and Current Research Characteristicsmentioning
confidence: 99%
“…For the #5 "gene regulation" cluster, an ML modality was adapted by Colbran et al to impute gene regulation information from genotype data and investigate 490 ancient Eurasian human DNA samples and explore divergent gene regulation mechanisms which contributed to skin pigmentation and metabolic and immune functions. The authors identified gene regulation roles in adaptation and associations between complex traits and genetic diversity Colbran et al, (2021). Atak et al devised a deep learning approach and integrative genomics strategy to analyze functional enhancer mutations with allelic imbalance of gene expression and chromatin accessibility and successfully interpreted and predicted the impact of a mutation on gene regulation Atak et al, (2021).…”
Section: The Knowledge Base and Current Research Characteristicsmentioning
confidence: 99%
“…As discussed in the Highlight feature on this article ( McGrath 2021b ), the study supports the idea that early developmental exposures can have persistent impacts on DNA methylation patterns in humans. In their study, John A. Capra and coauthors used a machine learning method to impute gene regulation patterns in DNA samples from ancient Eurasians ( Colbran et al 2021 ). They found differential regulation of genes involved in metabolism and the immune system among ancient populations with different diets and lifestyles.…”
mentioning
confidence: 99%